Ad

Hi,

a 6ya Technician can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repair professionals here in the US.

click here to Talk to a Technician (only for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

5x (-3x) = 2x -3x - -3x = 0

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

Jan 20, 2017 | The Office Equipment & Supplies

Since the y-variable is isolated in both equations, set the two right sides of the equations equal

x^2-7x+4=-8x^2+56x-86

Combine all like terms on one side of the equal sign

9x^2-63x+90=0. factor out the 9 to get** 9(x^2-7x+10)=0**

Now solve the equation**(x^2-7x+10)=0**. The solutions are x=5 and x=2

Calculate the y-value tof be y=-6

The two solutions are**(2,-6) and (5,-6)**

Graphically, here is how the two curves intersect. One intersection point in the screen capture is (2,-6). You can read that the other intersection point is (5,-6)

x^2-7x+4=-8x^2+56x-86

Combine all like terms on one side of the equal sign

9x^2-63x+90=0. factor out the 9 to get

Now solve the equation

Calculate the y-value tof be y=-6

The two solutions are

Graphically, here is how the two curves intersect. One intersection point in the screen capture is (2,-6). You can read that the other intersection point is (5,-6)

Mar 03, 2014 | Office Equipment & Supplies

We can write this polynomial as:

You can see this polynomial in following picture:

Notice that it intersects x axis for x=-2, 1 and 3 (because these are roots of polynomial).

- (x-(-2))*(x-1)*(x-3)=
- (x+2)(x-1)(x-3)=
- (x+2)[x*(x-3)-1*(x-3)]=
- (x+2)*(x^2-3x-x+3)=
- (x+2)(x^2-4x+3)=
- x*(x^2-4x+3)+2*(x^2-4x+3)=
- x^3-4x^2+3x+2x^2-8x+6=
- x^3-2x^2-5x+6

You can see this polynomial in following picture:

Notice that it intersects x axis for x=-2, 1 and 3 (because these are roots of polynomial).

Oct 03, 2011 | Office Equipment & Supplies

you have to make sure you are using the correct format for your drive i.e (+/-)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 8X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM, 4X BD-ROM, 4X BD-R, 2X BD-RE, 4X BD-ROM DL (double-layer), 4X BD-R DL (double-layer), 2X BD-RE DL (double-layer)
- Write: 24X CD-R, 16X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-RW, 6X DVD+RW, 5X DVD-RAM, 4X DVD+R DL (double-layer), 4X DVD-R DL (double-layer)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 6X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM
- Write: 24X CD-R, 24X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 6X DVD-RW, 8X DVD+RW, 5X DVD-RAM

Apr 09, 2011 | Acer Computers & Internet

8x-9- (x plus 1)=8x-9-x-1=8x-x-9-1=7x-10

Nov 27, 2010 | Casio FX-115ES Scientific Calculator

Solve for x

5x+3x+(-15) + 5 becomes 8x-10=180

move 10 from left to right and you get8x190

8x = 190

x = 23.75

so the first angle is (5*23.75)-15 = 103.75

and the second angle is (3*23.75) +5 = 76.25

check by adding 76.25+103.75 = 180

Make sense? I love math, let me know it you need more help

5x+3x+(-15) + 5 becomes 8x-10=180

move 10 from left to right and you get8x190

8x = 190

x = 23.75

so the first angle is (5*23.75)-15 = 103.75

and the second angle is (3*23.75) +5 = 76.25

check by adding 76.25+103.75 = 180

Make sense? I love math, let me know it you need more help

Mar 06, 2010 | SuperTutor Homeworkhelp.Com Super Tutor...

(4+x)(5-x)=(2+x)(7-x)

20-4x+5x-x^2=14-2x+7x-x^2

20+x=14+5x

20-14=4x

x=3/2:ans;

20-4x+5x-x^2=14-2x+7x-x^2

20+x=14+5x

20-14=4x

x=3/2:ans;

Oct 21, 2009 | SoftMath Algebrator - Algebra Homework...

the exact equation is

15x^2 - 21x - 18

=3(5x^2 - 7x - 6)

=3{5x^2 -(10-3)x -6 }

=3{5x^2 - 10x + 3x -6}

=3{5x(x - 2) + 3(x-2)}

=3(x-2)(5x+3) these are the factors

Thanks

Zulfikar Ali

ali_zulfikar@yahoo.com

9899780221

15x^2 - 21x - 18

=3(5x^2 - 7x - 6)

=3{5x^2 -(10-3)x -6 }

=3{5x^2 - 10x + 3x -6}

=3{5x(x - 2) + 3(x-2)}

=3(x-2)(5x+3) these are the factors

Thanks

Zulfikar Ali

ali_zulfikar@yahoo.com

9899780221

Oct 16, 2008 | SoftMath Algebrator - Algebra Homework...

(13)3/8-(6)15/16

Jun 17, 2008 | Texas Instruments TI-84 Plus Silver...

58 people viewed this question

Usually answered in minutes!

×